Produktionsskillnader och virkesskador med olika typer av matarvalsar - Dahl, Daniel (2006)
Earlier investigations showed that damages on timber from feeding rolls could be within the lower classes of damage according to VMRs classes. Knowledge about differences in productivity between kind types and aggressive types of feeding rolls is necessary because it should influence the question about damages on timber caused by different feeding rolls.